Cangpu Oral Liquid as a Possible Alternative to Antibiotics for the Control of Undifferentiated Calf Diarrhea - Wang, Shengyi; Cui, Dongan; Lv, Yanan; Yan, Zuoting; Zhang, Jiyu (Frontiers in Veterinary Science, 2022)
Antibiotics are essential in the prevention of calf diarrhea epidemics. As more antibiotics become ineffective due to drug-resistant bacteria, attention must be directed toward alternative treatments for calf diarrhea. Natural antibiotic alternatives, such as Chinese herbal medicine, have become a research hotspot in the clinical treatment of diseases such as calf diarrhea due to their characteristics of fewer side effects, low cost, little residue, and no drug resistance. The Cangpu Oral Liquid (CP) was modified from a traditional herbal formula that had been widely used in ancient China to treat gastrointestinal diseases in animals. In order to evaluate the treatment effect of CP on neonatal calf diarrhea, a randomized controlled field trial was performed. Two hundred and forty-six diarrheal Holstein calves of 2–15 days old were selected and randomly divided into two treatment groups receiving either apramycin or CP. 101 out of 123 calves recovered from diarrhea in the CP group, whereas 77 out of 123 calves showed recovery after antibiotic therapy. There were no differences in initial weight between both groups, while the final weight was significantly different (P = 0.892, P = 0.025, respectively). The mean average daily gain (ADG) of calves (211.45 gram/day) in the CP group was significantly higher compared to the antibiotic group (164.56 gram/day) (P = 0.001). The CP group also showed a shorter recovery time from diarrhea (3.90 days vs. 6.62 days, P = 0.001). The current results indicate that the CP has a beneficial clinical effect on the treatment of diarrhea in neonatal calves and is an effective alternative treatment option.